Alternative management for gynecological cancer care during the COVID‐2019 pandemic: A Latin American survey. Issue 3 (17th July 2020) - Rodriguez, Juliana; Fletcher, Angélica; Heredia, Fernando; Fernandez, Robinson; Ramírez Salazar, Heidy; Sanabria, Daniel; Burbano Luna, Javier; Guerrero, Eduardo; Pierre, Marc‐Edy; Rendón, Gabriel J.; Rosero, Indira; Trujillo, Lina María; et al.
Abstract: Objective: To determine the acceptance rate of treatment alternatives for women with either preinvasive conditions or gynecologic cancers during the COVID‐19 pandemic among Latin American gynecological cancer specialists. Methods: Twelve experts in gynecological cancer designed an electronic survey, according to recommendations from international societies, using an online platform. The survey included 22 questions on five topics: consultation care, preinvasive cervical pathology, and cervical, ovarian, and endometrial cancer. The questionnaire was distributed to 1052 specialists in 14 Latin American countries. A descriptive analysis was carried out using statistical software. Results: A total of 610 responses were received, for an overall response rate of 58.0%. Respondents favored offering teleconsultation as triage for post‐cancer treatment follow‐up (94.6%), neoadjuvant chemotherapy in advanced stage epithelial ovarian cancer (95.6%), and total hysterectomy with bilateral salpingo‐oophorectomy and defining adjuvant treatment with histopathological features in early stage endometrial cancer (85.4%). Other questions showed agreement rates of over 64%, except for review of pathology results in person and use of upfront concurrent chemoradiation for early stage cervical cancer (disagreement 56.4% and 58.9%, respectively). Conclusion: Latin American specialists accepted some alternative management strategies for gynecological cancer care during the COVID‐19 pandemic, which may reflect the region's particularities. The COVID‐19 pandemic led Latin American specialists to accept alternative management strategies for gynecological cancer care, especially regarding surgical decisions. Abstract : The COVID‐19 pandemic led Latin American specialists to accept alternative management strategies for gynecological cancer care, especially regarding surgical decisions.